Hypoglycemic Efficacy of Rh-aFGF Variants in Treatment of Diabetes in ZDF Rats - Zhang, Li; Zhou, Qingde; Chen, Min; Yang, Xuanxin; Lu, Chao; Sun, Wenzhe; Hui, Qi; Wang, Xiaojie (Frontiers in Cell and Developmental Biology, 2021)
Acidic fibroblast growth factor (aFGF) is a promising regulator of glucose with no adverse effects of hypoglycaemia. Previous researches revealed that aFGF mediated adipose tissue remodeling and insulin sensitivity. These findings supported rh-aFGF135 would be used as a new candidate for the treatment of insulin resistance and type 2 diabetes. In this study, we aimed to investigate the hypoglycemic efficacy of recombinant human acidic fibroblast growth factor 135 (rh-aFGF135) with low mitogenic in type 2 diabetic ZDF rats. ZDF rats were treated with rh-aFGF135 at a daily dosage of 0.25 and 0.50 mg/kg by tail intravenous injection for 5 weeks. The blood glucose levels, oral glucose tolerance test, insulin tolerance test, HOMA-IR for insulin resistance, serum biochemical parameters and the histopathological changes of adipose tissue, liver and other organs were detected at designed time point. The glucose uptake activity and anti-insulin resistance effect of rh-aFGF135 were also detected in HepG2 cells. Results revealed that rh-aFGF135 exhibited a better hypoglycemic effect compared with vehicle group and without the adverse effect of hypoglycaemia in ZDF rats. Compared with vehicle group, rh-aFGF135 significantly improved the situation of hyperglycemia and insulin resistance. Rh-aFGF135 decreased ALT, AST, GSP and FFA levels noticeably compared with vehicle control group (P< 0.01 or P< 0.001). After 5 weeks of treatment, high-dosage rh-aFGF135 could remodel adipose tissue, and has no influence on other organs. H&E staining showed that rh-aFGF135 reduced the size of adipocytes. In addition, rh-aFGF135 may improve insulin resistance partly by increasing the protein expression of p-IRS-1 (human Ser 307). As a hypoglycemic drug for long-term treatment, rh-aFGF135 would be a potentially safe candidate for the therapy of type 2 diabetes.